TESTING THE INTEGRITY OF REINFORCED CONCRETE PILES AT THE EXIT PORTAL OF THE KOBILJA GLAVA TUNNEL USING A NON-DESTRUCTIVE METHOD - Ekrem Bektašević; Satko Filipović; Kemal Gutić; Namik Musa (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta)
Testing the integrity of piles is a key aspect of geotechnical analysis, and the application of non-destructive methods allows for a reliable assessment of the condition of piles without causing physical damage to the structure. This paper focuses on the application of the Pile Echo Test (PET) method for verifying the mechanical properties and quality of piles that serve as supports for portal structures. The testing showed that the measured velocities ranged from 4000 to 5000 m/s, with amplifications between 25% and 35%, indicating that the piles do not have serious structural issues and that no material degradation has occurred that would affect the load-bearing capacity or stability of the piles. By using the PET method, the integrity of the piles can be precisely determined, thereby enhancing the safety and long-term stability of portal structures. The results of this study confirm the importance of applying this method in geotechnical analyses as a reliable technique for verifying the quality of piles.